Medical Management in Focal versus Generalized Epilepsy - Sannagowdara, Kumar; Khan, Nadir (Journal of Pediatric Epilepsy, 2021)
About 70% of children with new-onset epilepsy have the potential to become seizure-free on antiepileptic drug (AED) monotherapy with appropriately selected first-line medication. In ideal world, physician is expected to achieve best possible seizure control without impacting the quality of life. There is rapid increase in number of AEDs available over last couple of decades. Although not necessarily all of them are superior to old generation drugs in terms of seizure control, certainly there is change in landscape from perspective of tolerability and side-effect profile. Physicians must therefore be familiar with safety, tolerability, therapeutic effects, synergistic combinations as well as AEDs to avoid in specific circumstances. The article attempts to give general overview of available AEDs under broad umbrella of effectiveness against focal and generalized seizures as well as drugs with “broad spectrum.” The emergence of newer AEDs with broad spectrum and favorable side-effect profile is welcome. However, the future lies in better understanding of underlying diverse pathophysiology of clinical symptom “epilepsy” and developing new compounds acting on molecular targets as well as individualizing therapy. Technological advances in molecular genetics research are bringing precision medicine to the fore.
Keywords: epilepsy; generalized seizures; focal seizures; antiepileptic drug